(untitled) (Journal of Partial Differential Equations, 2005)
In this paper, the singular semilinear elliptic equation Δu + q(x)u^α + p(x)u^-β - h(x)u^-ϒ = 0, x ∈ R^N, N ≥ 3, is studied via the super and sub-solution method, where Δ is the Laplacian operator, α ∈ [0, 1), β > 0, and ϒ ≥ 1 are constants. Under a set of suitable assumptions on functions q(x), p(x) and h(x), it is proved that there exists for the equation one and only one minimal positive entire solution.